Models of forecasting the loss of financial strength as a component of the system of economic security of contracting enterprises - Izmaylova, E.; Bolila, N. (Ways to Improve Construction Efficiency, 2018)
The article reviews Ukrainian and foreign models of forecasting financial stability, which can be used by management of construction companies. It is determined that forecasting financial stability is an important component of the economic security system of a construction company. Analysis of the literature has revealed that the most common methods of assessing financial stability today are the method of coefficients and multifactor models based on the use of correlation-regression analysis. The necessity of using modern information technologies for the formation of the system of economic security of enterprises is substantiated.